Aplikasi Pengawasan Antar-Jemput Anak Sekolah Menggunakan API (Application Program Interface) Whatsapp - Sardi, Hajra; Jasril, Jasril; Irsyad, Muhammad; Kurnia Gusti, Siska (STMIK Budi Darma, 2024)
Alfatih School Indonesia is the first Islamic school with a combination of Indonesia and Turkey which was founded on August 15 2019. This school always ensures that its students are safe from going to school to leaving school, but currently the school only carries out supervision by waiting and ensuring that only parents students who are allowed to pick up students. This method is less effective because there is no accurate documentation or records, besides that many crimes occur, such as kidnapping, which means that security must be improved. In this research, an Android-based school children pick-up and drop-off monitoring application was built using the WhatsApp API with the QR Code feature. The application that was built is equipped with the main feature of Whatsapp Information, namely a feature that allows parents to receive detailed information about the person who picked up their child via Whatsapp messages sent to the parents' Whatsapp number by the application automatically. The type of WhatsApp that will be used is the WhatsApp API (Application Program Interface). The message will be sent after the school confirms it using a scan of the QR Code that each parent has. To ensure security the generated QR Code will always be different and can only be created through the application. The application built can also validate invalid QR-Code